Generation of three human iPSC lines from PLAN (PLA2G6-associated neurodegeneration) patients - Machuca, Candela; Correa-Vela, Marta; García-Navas, Deyanira; Darling, Alejandra; Villalón-García, Irene; Sánchez-Alcázar, José Antonio; Pérez-Dueñas, Belén; Erceg, Slaven; Espinós, Carmen (Stem cell research, 2021)
The human iPSC cell lines, PLANFiPS1-Sv4F-1 (RCPFi004-A), PLANFiPS2-Sv4F-1 (RCPFi005-A), PLANFiPS3-Sv4F-1 RCPFi006-A), derived from dermal fibroblast from three patients suffering PLAN (PLA2G6-associated neurodegeneration; MIM 256600) caused by mutations in the PLA2G6 gene, was generated by non-integrative reprogramming technology using OCT3/4, SOX2, CMYC and KLF4 reprogramming factors. The pluripotency was assessed by immunocytochemistry and RT-PCR. Differentiation capacity was verified in vitro. This iPSC line can be further differentiated toward affected cells to better understand molecular mechanisms of disease and pathophysiology.
Keywords: Cell Line; přeprogramování buněk; fosfolipasy A2, skupina VI; buněčné linie; mutace; buněčná diferenciace; indukované pluripotentní kmenové buňky; Cell Differentiation; Cellular Reprogramming; Group VI Phospholipases A2; Humans; Induced Pluripotent Stem Cells; Kruppel-Like Factor 4; Mutation; Neuroaxonal Dystrophies; lidé; Krüppel-like faktor 4; neuroaxonální dystrofie